FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO EKUITAS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Y.A. DIDIK CAHYANTO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The aim of research to obtain empirical evidence that the asset growth, financial leverage, size, operating leverage, liquidity and dividend payout ratio affect the equity risk. Samples of this research are companies registered in LQ 45, which is based on a purposive sampling method. Asset Growth, Financial Leverage, Operating Leverage, Liquidity and Dividend Payout Ratio have no effect on the risk of equity, either in 2001, 2002 and 2003. Size does not affect the equity risk in 2001 and 2003. While in 2002 the size effect on the equity risk.